The witch tree symbol - Keene, Carolyn (New York : Grosset & Dunlap, 1975)
An unusual hex sign leads Nancy Drew to Pennsylvania Dutch country in pursuit of a thief who stops at nothing to get rid of her.
Keywords: Amish -- Fiction; Mystery and detective stories